Penguatan kepatuhan dan reputasi lembaga keuangan syariah melalui implementasi manajemen risiko - febrian, Neyzha Virela Lourencia (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze how the implementation of effective risk management in Islamic financial institutions can strengthen compliance with sharia regulations and principles. As well as maintaining the reputation of Islamic Financial Institutions. This study uses secondary data from various sources used in the form of journals, previous research, books and websites on Islamic banking. The results of this study indicate that effective and optimal risk management can strengthen the compliance of Islamic financial institutions with sharia principles and maintain the reputation (image) of a financial institution. Risk management is also a strategic foundation for developing credible, accountable and trusted institutions in the long term.